A qualidade dos serviços educacionais e a proteção do código de defesa do consumidor - Duarte, Clotildes Fagundes [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
A qualidade dos Serviços Educacionais e a proteção do Código do Consumidor é o objeto de estudo nesta pesquisa. O binômio lucratividade X qualidade na educação nacional tem emergido como uma fonte de preocupação pelos órgãos normatizadores e fiscalizadores deste setor, bem como por toda sociedade civil. Face a esta constatação, pretende a presente pesquisa demonstrar que, o ensino privado, além de submeter-se à todas normativas da educação nacional e da autorização e avaliação da qualidade pelo Poder Público, como um imperativo constitucional e infra-constitucional, deve atender ainda aos princípios da ordem econômica e do Código de Defesa do Consumidor, posto que serviço remunerado. Considerando a extensa subjetividade do conceito qualidade, a presente pesquisa busca nos indicadores Legais e Institucionais, a moderna concepção de Qualidade de Ensino. Nesta esteira, o estudo apresenta suporte teórico para afirmar a possibilidade jurídica da aplicabilidade do Direito do Consumidor às relações de consumo do Ensino, não apenas no que se refere aos custos, preços e propaganda enganosa, mas sobretudo em relação à qualidade do Ensino ministrado, coibindo os excessos de lucratividade advindos da falta do comprometimento com o caráter social inerente à Educação. Desta forma, está o prestador de Ensino, a exemplo dos demais prestadores de serviços no mercado, obrigado a oferecer serviços adequados para os fins que razoavelmente deles se esperam, bem como serviços que atendam as normas regulamentares de prestabilidade, sob pena da competente ação de responsabilidade pelos vícios de qualidade, conforme permissivo contido no Código de Defesa do Consumidor.

The providing Education Services under The protection of the Consumer Rights Actwith the emphasis on responsibility for the imperfections of the Quality of education services is the objective of this research. The question of profit versus quality in the National Education System has emerged as a source of worry of the Education Agencies responsible for the regulation and control of this sector, as well as for society as a whole. Considering these facts is the intention of this research. We intend to demonstrate that the private educational system not only complies with all the regulations of the Official Educational System, but also with the authorization and evaluation of quality by the public Administration. Within the role of that body at a constitutional and sub-constitutional level as well as adhering to economic principles and Consumer Rights, as a paid service. Taking into consideration the subjective nature of the concept quality, this research aims to present, using both legal and institutional indicators, a modern concept of Teaching Quality. In this way, the study presents theoretical support to ratify the judicial possibility of the applicability of consumer rights in relation to the consumption of Education and Teaching. Not only related to costs, princes and deceptive advertising, but especially in relation to the quality of teaching administered. Restraining excessive profits that occur as a consequence of the lack of compromise with the social character inherent to Education. In this way the education service is, as much as any other service on the market, compelled to offer appropriate services for the objectives within reasonably expected standards, as well as services that comply with the principles of services rendered regulations by using competent action of responsibility in providing quality without viciousness in quality, according to directives included in the Consumer Rights Code.
Keywords: Consumidores - Educação; Proteção e defesa do consumidor - Legislação; Ensino privado; Responsabilidade (Direito); Prestação de serviços; Vício De Qualidade; Consumidor de Ensino; Private Tuition; Civil Law Responsibility; Quality Vices; Educational Consumer; Services Rendered